Russia’s Hybrid Warfare in Ukraine Threatens Both Healthcare & Health Protections Provided by International Law - Baker, Michael S.; Baker, Jacob; Burkle, Frederick M. (Annals of global health, 2023)
Hybrid Warfare is on display because of the unjustified Russian invasion of Ukraine. This is characterized by numerous crimes against civilians as seen vividly during the occupation of the town of Bucha where rape, torture, murder, and looting seem to reflect Russian military policy, leadership, and command guidance. Of particular concern is the threat to hospitals and health care as well as vital life support. Numerous hospitals have been damaged and destroyed. Hospitals are not tactical military targets and targeting health care facilities and personnel ignores traditional jus in bello and ignores numerous conventions established to stabilize the global order. The Russian-proclaimed "special operation" in Ukraine has been characterized by barbarian warfare in which the Russian military uses weapons against the civilian population and civilian infrastructure. The aggressors have embarked on a purposeful terror campaign through infrastructure attacks, which are of little military value except to demoralize the nation's people. This is evident with Russian missile and drone attacks on electric, water, and health care in Ukraine. Warfare now and in the future may be increasingly aimed at demoralizing civilian populations and reducing the will of the people and their government to resist. The Ukrainian invasion clearly shows that this use of hybrid warfare should be met with a strong reaction of the international community at the earliest possible stage, especially the supposedly peace-loving neutral countries, or else the future is expanded unlawful and barbaric military conflict.